Epidemiology and detection of HIV-1 among pregnant women in the United Kingdom: results from national surveillance 1988-96. Issue 7127 (24th January 1998) - Nicoll, Angus; McGarrigle, Christine; Brady, Anthony R; Ades, A E; Tookey, Pat; Duong, Trinh; Mortimer, Janet; Cliffe, Susan; Goldberg, David; Tappin, David; Peckham, Catherine; Hudson, Chris
Abstract: Objective: To describe the epidemiology of HIV-1 infection in pregnant women in the United Kingdom. Design: Serial unlinked serosurveillance for HIV-1 in neonatal specimens and surveillance through registers of diagnosed maternal and paediatric infections from reporting by obstetricians, paediatricians, and microbiologists. Setting: United Kingdom, 1988-96. Subjects: Pregnant women proceeding to live births and their children Main outcome measures: Time trends in prevalence of HIV-1 seropositivity in newborn infants (as a proxy for infection in mothers); the proportions of mothers with diagnosed HIV-1 infections, and their characteristics. Results: HIV-1 prevalence among mothers in London rose sixfold between 1988 and 1996 (0.19% of women tested; 1 in 520 in 1996). Apart from in Edinburgh and Dundee, levels remained low in Scotland (0.025%; 1 in 3970) and elsewhere in the United Kingdom (0.016%; 1 in 1930). Over a third of births to infected mothers in 1996 occurred outside London. In London the reported infections were predominantly among black African women, whereas in Scotland most were associated with drug injecting. The contribution of reported infection among African women increased over time as that of drug injecting declined. In Scotland 51% of mothers' infections were diagnosed before the birth. In England, despite a national policy initiative in 1992 to increase the antenatal detection rate of HIV, no improvement in detection was observed, and in 1996 only 15% of previously unrecognised HIV infections were diagnosed during pregnancy. Conclusions: HIV-1 infection affects mothers throughout the United Kingdom but is most common in London. Levels of diagnosis in pregnant women have not improved. Surveillance data can monitor effectively the impact of initiatives to reduce preventable HIV-1 infections in children.